2022
DOI: 10.3390/brainsci12050602
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Techniques as Descriptive and Diagnostic Tools for Infants at Risk for Autism Spectrum Disorder: A Systematic Review

Abstract: Autism Spectrum Disorder (ASD) has traditionally been evaluated and diagnosed via behavioral assessments. However, increasing research suggests that neuroimaging as early as infancy can reliably identify structural and functional differences between autistic and non-autistic brains. The current review provides a systematic overview of imaging approaches used to identify differences between infants at familial risk and without risk and predictive biomarkers. Two primary themes emerged after reviewing the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Individuals with autism often exhibit atypical perceptual and neural processing of emotional information, including emotional prosodic voices (Kuhl et al, 2005;Lindström et al, 2018;Van Lancker et al, 1989;Wang et al, 2007; for comprehensive reviews, see Frühholz & Staib, 2017;Yeung, 2022). While previous studies have indicated that social-emotional behavioral indicators typically begin to demonstrate predictive power for autism from the second year of life (Gliga et al, 2014;Jones et al, 2014), brain functional indicators of emotional processing during infancy, especially within the first year of life, have already shown their predictive value (Ayoub et al, 2022;Clairmont et al, 2021;Molnar-Szakacs et al, 2021). For instance, infants subsequently diagnosed with autism displayed a smaller amplitude and shorter duration of the negative central (Nc) component at six months of age when viewing smiling faces compared to toys, a pattern not observed in infants who were subsequently undiagnosed (Jones et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with autism often exhibit atypical perceptual and neural processing of emotional information, including emotional prosodic voices (Kuhl et al, 2005;Lindström et al, 2018;Van Lancker et al, 1989;Wang et al, 2007; for comprehensive reviews, see Frühholz & Staib, 2017;Yeung, 2022). While previous studies have indicated that social-emotional behavioral indicators typically begin to demonstrate predictive power for autism from the second year of life (Gliga et al, 2014;Jones et al, 2014), brain functional indicators of emotional processing during infancy, especially within the first year of life, have already shown their predictive value (Ayoub et al, 2022;Clairmont et al, 2021;Molnar-Szakacs et al, 2021). For instance, infants subsequently diagnosed with autism displayed a smaller amplitude and shorter duration of the negative central (Nc) component at six months of age when viewing smiling faces compared to toys, a pattern not observed in infants who were subsequently undiagnosed (Jones et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we investigated the predictive value of brain morphology in TD for the continuous distribution of autistic traits. Brain imaging has often been applied in ASD to describe functioning and to identify potential risk markers (e.g., [ 41 , 42 ]). We found that autistic traits correspond to subtle autism-related alterations in brain morphology in typically developing individuals, as well as lying on a continuum in the general adolescent population, even at levels below a clinically revenant cut-off.…”
Section: Discussionmentioning
confidence: 99%
“…At least four ferroptosis-related genes (FRGs) have been linked with the likelihood, in the AUC (Area Under the Curve) values of ROC (Receiver Operating Characteristic) curves, of developing autism, particularly if involving the regulatory genes RORA (Related Orphan Receptor A), FAF1 (Fas-associated Factor 1), the microRNA gene miR-4703-3p, NFYB (Nuclear Transcription Factor Y Subunit Beta) and the microRNA miR-6073 ( 74 ). Nevertheless, genetics is not so routinely available, whereas neuroimaging might be much more affordable and available ( 75 ) and early motor signs ( 76 ).…”
Section: Oral Health Prevention In the Autistic Subject As Early As P...mentioning
confidence: 99%